Macroscopic and Microscopic Diagnosis of Three Entandrophragma Species Traded in Türkiye - Kamile Tırak Hızal; Nihan Koçer (BioResources, 2024)
The anatomical characteristics are highlighted for Entandrophragma cylindricum, Entandrophragma utile, and Entandrophragma angolense. Wood samples, which were previously obtained from commercial timber industries in the Marmara region of Türkiye and used as course materials, were used. Qualitative and quantitative anatomical characteristics were determined. Qualitatively, characters such as distinct growth rings, diffuse-porous wood, deposits in vessel elements, simple perforation plates, alternate intervessel pits, heterogeneous ray type, and septate fibres, were common to all species. The quantitative evaluation showed that there were differences between species. Entandrophragma species differ in some wood characteristics such as the tangential diameter of the vessel, ray height, ray width, and fibre lumen diameter. E. utile had higher values of the mean tangential vessel diameter (180 μm) and fiber lumen diameter (18.4 μm) than the other two species. It is possible to say that the anatomical features of E. cylindricum differ from that of other species and that it will be easier to diagnose among other species. E. cylindricum had the lowest values of the mean tangential vessel diameter (147 μm) and ray height (361 μm).  Distinctive characters for E. utile and E. angolense are tangential vessel diameter, vessel length, ray height, ray width, and all fibre dimensions.